"Mów, niezapomniany Hiobie!". Portret cierpiącego Hioba (Kierkegaard - Wojtyła - Fedoryszyn) = "Speak, unforgettable Job!". Portrait of suffering Job (Kierkegaard - Wojtyla - Fedoryszyn) - Radziszewski, Stefan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Job is the title character of the drama by K. Wojtyla and a character of the Repetition by S. Kierkegaard. Wojtyla presents a parable about the suffering that affects the individual, but also the whole nation and the world. Job`s longing to save the past happiness brings the final picture of the coming of the Messiah who is the only one to satisfy Job`s hunger for happiness.
Keywords: Jan Paweł II, papież (1929-2005); Kierkegaard, Soren (1813-1855); Fedoryszyn, Jarosław (1955-2020); dramat polski-20 w.; filozofia chrześcijańska - 19 w.; inscenizacja teatralna